1996
DOI: 10.1007/bf02281230
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of 2-Amino-5-(1-methyl-5-nitro-2-imidazolyl)-1,3,4-thiadiazol (Megazol) and related compounds: A concerted study using X-ray crystallography, molecular mechanics, and semiempirical methods

Abstract: A structural study of three nitroimidazoles was carried out using molecular mechanics, semiempirical methods, and X-ray crystallography. Structural features which might account for the high efficiency of 1 (Megazol) as an antiparasitic drug and its opposite, the inactivity of its regiomers 2 and 3 were examined, i.e., coplanarity of the two rings, preferred conformations, and rotational barriers around the pivot bond between the two rings. For the three compounds an antiperiplanar conformation is preferred for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Alternatively, the difference in biological efficacy of 4-substituted derivatives may rely on the change in structure of the compound that no longer would be planar owing to steric interactions between the substituent at position 4 and the nitro group. As we showed previously, the most efficient compound in the series, megazol, has a planar structure, a feature that might be a requirement for delocalization and consequently for the optimized half-life of the nitro radical anion.
1 Bioreduction Routes for Nitro Compounds
…”
Section: Discussionmentioning
confidence: 68%
“…Alternatively, the difference in biological efficacy of 4-substituted derivatives may rely on the change in structure of the compound that no longer would be planar owing to steric interactions between the substituent at position 4 and the nitro group. As we showed previously, the most efficient compound in the series, megazol, has a planar structure, a feature that might be a requirement for delocalization and consequently for the optimized half-life of the nitro radical anion.
1 Bioreduction Routes for Nitro Compounds
…”
Section: Discussionmentioning
confidence: 68%
“…Substitution at position 4 either abolished or diminished activity against Trypanosomatidae; it could be related to the loss of planarity of the system as previously shown [56]. What is more, an isomer of Megazol with the nitro group at position 4 was inactive something already noticed for other nitroimidazoles [57].…”
Section: 11-nitroimidazolementioning
confidence: 64%
“…Spigelman et al (1986) suggested that the structure of suramin may disturb cell membrane surfaces and modify the tight junctions of the blood-brain barrier, thereby facilitating the subsequent penetration of the nitroimidazoles. Rameau et al (1996) showed that megazol has a planar structure, thus giving a good opportunity for a stacking complex formation between megazol and suramin, also in vivo. It is therefore tempting to hypothesize that suramin and megazol act synergistically at the level of the blood-brain barrier.…”
Section: (B)mentioning
confidence: 99%